EVALUASI KINERJA JARINGAN IRIGASI SEBAGAI USULAN DALAM KEGIATAN PEMELIHARAAN DAN PENENTUAN PRIORITAS PENANGANAN KERUSAKAN (Studi Kasus : Saluran Sekunder Daerah Irigasi Cihaur, Kabupaten Cilacap, Jawa Tengah) - , Edwin Martha P; , Prof. Dr. Ir. Bambang Agus Kironoto ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The maintenance of the irrigation network in the region of DI. Cihaur currently can not be done well , due to budget constraints is a major problem faced by the OP SDA II BBWS Citanduy as the manager . To overcome this problem , we need an additional parameter as a reference in determining the priority of handling damage so that available funds can be allocated optimally to restore the function of the irrigation network . In this study , records of tissue damage irrigation search results obtained from the OP SDA II is used as a basic reference for determining the percentage of the physical condition based on the Regulation of the Minister of Public Works No. : 32/PRT/M/2007 . Percentage of the value of the physical conditions obtained were then determined rehabilitation treatment recommendations refer to the Policy Department of Public Works Director General of the SDA 2007. Network performance evaluation activities conducted on secondary channels that require rehabilitation mild and moderate , by calculating the discharge of each segment to determine the rate of water loss and water delivery efficiency in each secondary channel . In this study, also conducted an evaluation to determine the factors that cause damage to the channel , as well as the evaluation of rehabilitation activities that have been carried out by the manager . The results obtained from the performance evaluation of a proposed network in setting policy priorities related to the handling of secondary channels making it useful in optimizing the availability of existing budget . It is expected that this research can provide benefits both in the operation and maintenance of irrigation networks , improved welfare of farmers , as well as an increase in food production.